City Diplomacy Practices Towards China and the United States in the Western Balkans. Examples from Croatian and Slovenian Cities - Michał Gzik; Marcin Frenkel (Studia Regionalne i Lokalne)
Cities are becoming more important actors in the international arena because they have competencies that enable them to conduct foreign activities. This phenomenon is the result of far-reaching processes of globalisation and the pluralisation of actors in international relations. This study presents a map of partnerships between six Croatian and two Slovenian cities and their Chinese and American partners, as well as a description of the thematic areas of such cooperation. Moreover, based on the results of our survey, we indicate similarities and differences in the patterns of cooperation between the cities of the Western Balkans and their foreign partners, referring to the multilevel governance theory.